Tanakh = [Tanakh] : a new translation of the Holy Scriptures according to the traditional Hebrew text. (Jewish Publication Society, 1985)
The Tanakh is an entirely original translation of the Holy Scriptures into contemporary English, based on the Masoretic--the traditional Hebrew--text.